Length and Weight Relationships in Two Species of Sea Snakes from Tamilnadu South East Coast of India - Damotharan, P (International Journal of Pharmaceutical & Biological Archive, 2014)
Length and Weight Relationships in Two Species of Sea Snakes from Tamilnadu South East Coast of India